An Investigation of Hydrocolloids Film Forming Ability on a Vertically Rotating Disc (Chemical Engineering Research Bulletin, 2023)
Hydrocolloids are widely used in the food industry to perform variety of functions such as coatings, thickening, emulsifying, stabilizing and edible films. Their functionality for a given application are underpinned by the molecular weight, shape, and conformation in aqueous solution. The film forming ability of selected hydrocolloids, different in shape (rod, random coil and spherical) and/or conformation in aqueous solution were investigated experimentally and numerically on a vertically rotating disc. These include: xanthan, pectin, carboxymethyl cellulose (CMC) and gum arabic. The Laser scan method was used for the measurement of film thickness of the respective the hydrocolloids. The Volume of Fluid (VOF) Computational Fluid Dynamics (CFD) modelling approach was used in the numerical model. The variation in film formation at different concentrations has been observed to ascertain a trend. Both the experimental and simulation results revealed that the film formation depends on the molecular structure of the hydrocolloid while viscosity and rotating speed significantly influenced the film thickness. Xanthan showed higher film formation ability compared to the other hydrocolloids due to its higher viscosity. It was interesting to note that the film formation ability by CMC was significantly higher than pectin though pectin was five times more viscous than CMC. Gum arabic exhibited the lowest viscosity but formed almost the same film thickness on the disc as pectin despite being twenty times less viscous. Increasing CMC concentration from 0.5% to 1% resulted in increasing its viscosity and the film thickness. The film thickness increased at the disc rotating speed of 6 rpm as compared to 3 rpm. The simulation results were in good agreement with the experimental data.Chemical Engineering Research Bulletin 23 (2023): 103-107